2022
DOI: 10.1186/s12873-022-00722-5
|View full text |Cite|
|
Sign up to set email alerts
|

Emergency medical care of patients with psychiatric disorders -  challenges and opportunities: Results of a multicenter survey

Abstract: Background Pre-clinical psychiatric emergencies are generally treated by emergency medical staff. The subsequent clinical treatment is often conditioned by interaction problems between emergency medical staff and psychiatric clinical staff. Objectives To identify problems affecting interaction between emergency medical and psychiatric care of mentally ill patients and pinpoint aspects of optimized emergency care. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
13

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 28 publications
0
15
0
13
Order By: Relevance
“…Therefore, we designed a questionnaire after conducting a thorough literature review and gathering relevant questions from previous studies. [12][13][14]16,20 The questionnaire was reviewed by two emergency consultants and two psychiatric consultants for content and face validity, practicability, and interpretation of answers. Then, to ensure the quality of the questions, an emergency consultant and a psychiatric consultant reviewed the questionnaire to assess the practicability, validity, and interpretation of answers.…”
Section: Study Assessment Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we designed a questionnaire after conducting a thorough literature review and gathering relevant questions from previous studies. [12][13][14]16,20 The questionnaire was reviewed by two emergency consultants and two psychiatric consultants for content and face validity, practicability, and interpretation of answers. Then, to ensure the quality of the questions, an emergency consultant and a psychiatric consultant reviewed the questionnaire to assess the practicability, validity, and interpretation of answers.…”
Section: Study Assessment Toolsmentioning
confidence: 99%
“…The study found that 36.7% of EPs do not believe that they are adequately qualified to treat PEs and, remarkably, that many of them would seek telephone contact with acute psychiatric hospitals. 13 A survey conducted in the US Midwest to assess EPs’ attitudes and practices found that 39.5% of them also feel inadequately trained to manage PEs, while 92.3% said that additional mental health resources would be beneficial for their facility. 14 In India, 83.8% of the physicians examined in one study said that there are no mental health policies in their departments.…”
Section: Introductionmentioning
confidence: 99%
“…Psychiatrische NFR verlangen von Rettungskräften über ihre notfallmedizinischen Kompetenzen hinaus Einfühlungsvermögen und die Fähigkeit deeskalierend zu agieren [40]. Über Fortbildungen hinaus [41]…”
Section: Fazitunclassified
“…Psychiatrische NFR verlangen von Rettungskräften über ihre notfallmedizinischen Kompetenzen hinaus Einfühlungsvermögen und die Fähigkeit deeskalierend zu agieren 40 . Über Fortbildungen hinaus 41 muss das Management psychiatrischer Notfälle daher ein integraler Bestandteil der Ausbildung von Rettungsfachpersonal und Notärzt*innen sein.…”
Section: Fazitunclassified
“…Their essential characteristics are therefore the severity, the need for intervention and his speed ( Wheat et al, 2016 ). Faced with an urgency, it is first essential to exclude the organic causes that could have caused it, from hormonal and metabolic imbalances to acute neurological and inflammatory conditions ( Schick et al, 2022 ). Subsequently, psychiatric disorders that can give rise to situations of urgency must be considered: psychomotor agitation, acute psychoses, manic episodes, suicidal intentionality and severe behavioral alterations ( Salani et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%